2011
DOI: 10.1016/j.bbamcr.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Rin-like, a novel regulator of endocytosis, acts as guanine nucleotide exchange factor for Rab5a and Rab22

Abstract: RIN proteins serve as guanine nucleotide exchange factors for Rab5a. They are characterized by the presence of a RIN homology domain and a C-terminal Vps9 domain. Currently three family members have been described and analyzed. Here we report the identification of a novel RIN family member, Rin-like (Rinl), that represents a new interaction partner of the receptor tyrosine kinase MuSK, which is an essential key regulator of neuromuscular synapse development. Rinl is localized to neuromuscular synapses but show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 49 publications
(62 reference statements)
3
30
0
Order By: Relevance
“…We found that RINL/WT interacted with dominant-negative Rab5b/S34N using the yeast two-hybrid system as reported previously [14], while either RINL/DP_AA or YT_AA reduced this interaction (data not shown). Furthermore, the increase in GTP-Rab5b after co-expression of RINL was completely abolished by mutations of the VPS9 domain (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…We found that RINL/WT interacted with dominant-negative Rab5b/S34N using the yeast two-hybrid system as reported previously [14], while either RINL/DP_AA or YT_AA reduced this interaction (data not shown). Furthermore, the increase in GTP-Rab5b after co-expression of RINL was completely abolished by mutations of the VPS9 domain (Fig.…”
Section: Resultssupporting
confidence: 87%
“…Quite recently, RINL was reported to act as a GEF for both Rab5 and Rab22 GTPases in vitro , stimulating the dissociation rate of GDP from these GTPases [14]. We confirmed the GEF activity of RINL for Rab5 subfamily proteins by measuring the formation of GTP-bound forms of these proteins (Figure S1).…”
Section: Resultssupporting
confidence: 78%
“…Rab11 S25N was provided by Dr M. Granato (University of Pennsylvania, Philadelphia, PA, USA). Rab5 was cloned into pEGFP‐C2 (Clontech, Palo Alto, CA, USA) using Eco RI . SBP‐MuSK (wt) was generated by introducing the SBP sequence into a 10 amino acid alternative insert in the extracellular domain of MuSK by PCR.…”
Section: Methodsmentioning
confidence: 99%
“…In the absence of Rabex-5, Rab22 and Rab5 show only partial colocalization, whereas cells overexpressing both Rab22 and Rab5 exhibited enlarged endosomes, suggesting that these two Rab GTPases work cooperatively in the regulation of endosome fusion and the trafficking of epidermal growth factor receptors (28). A recent study demonstrated that RIN (Ras and Rab interactor) family protein Rin-like (Rinl) binds to the nucleotide-free form of Rab5a and Rab22, and Rinl has GEF activity toward both proteins, but it acts with higher efficiency on Rab22 (29). The functional relationship between Rin1 and Rabex-5 is not currently known.…”
Section: Guanine Nucleotide Exchange Factor Cascadesmentioning
confidence: 99%